Anodic oxidation of formaldehyde on Pt-modified SnO2 thin film electrodes prepared by a sol-gel method - Villullas, H. M.; Mattos-Costa, F. I.; Nascente, PAP; Bulhoes, LOS (Elsevier B.V., 2004)
Pt-modified SnO2 electrodes were prepared onto titanium substrates in the form of thin films of similar to2 mum at different temperatures in the range from 200 to 400degreesC. Surface morphology was examined by scanning electron microscopy (SEM). It was found that Pt-SnO2 sol-gel layers are significantly rough and have a low porosity. X-ray diffraction (XRD) studies showed that the films consist of Pt nanoparticles with average size varying from about 5 to 10 nm, depending on the preparation temperature, and amorphous tin oxide. X-ray photoelectron spectroscopy (XPS) was employed to determine the superficial composition of the electrodes and demonstrated the presence of Sn4+ in all the samples. XPS spectra of the Pt 4f electrons showed the presence of Pt in the zero-valence state as well as in ionic forms. The general electrochemical behavior was characterized by cyclic voltammetry in 1 mol l(-1) HClO4 and the electrocatalytic activity towards the oxidation of formaldehyde was investigated by potential sweeps and chronoamperometry. The results obtained show that the Pt-SnO2/Ti system exhibits a significant catalytic activity for the oxidation of formaldehyde, with an onset potential below 0.1 V. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: formaldehyde oxidation; Pt nanoparticles; Pt-modified oxide; tin oxide; sol-gel films